1999
DOI: 10.1074/jbc.274.36.25398
|View full text |Cite
|
Sign up to set email alerts
|

Purification of Mlc and Analysis of Its Effects on the pts Expression in Escherichia coli

Abstract: Products of the pts operon of Escherichia coli have multiple physiological roles such as sugar transport, and the operon is controlled by two promoters, P0 and P1. Expression of the pts P0 promoter that is increased during growth in the presence of glucose is also activated by cAMP receptor protein⅐cAMP. Based on the existence of a sequence that has a high similarity with the known Mlc binding site in the promoter, the effects of the Mlc protein on the pts P0 promoter expression were studied. In vivo transcrip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
70
0

Year Published

2004
2004
2015
2015

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 55 publications
(70 citation statements)
references
References 27 publications
(37 reference statements)
0
70
0
Order By: Relevance
“…CRP concentrations seem to be less important during such dynamic processes and might be more important for long term adaptation to different growth substrates. It has been reported that the pts operon is regulated by cAMP⅐CRP as well as by Mlc (30,31). This regulation is weak (factor of 2-3) (32) and hence has often been neglected.…”
Section: Discussionmentioning
confidence: 99%
“…CRP concentrations seem to be less important during such dynamic processes and might be more important for long term adaptation to different growth substrates. It has been reported that the pts operon is regulated by cAMP⅐CRP as well as by Mlc (30,31). This regulation is weak (factor of 2-3) (32) and hence has often been neglected.…”
Section: Discussionmentioning
confidence: 99%
“…Cloning is described in SI Materials and Methods. Expression and purification of EIIB proteins and wild-type and mutant Mlc proteins with a single amino acid change were performed as described previously (7,12). Whereas wild-type and mutant Mlc proteins with a single amino acid change were insoluble in 10 mM Tris⅐HCl buffer (pH 7.5) containing 1 mM DTT, Mlc harboring two point mutations (Arg306Gly and Leu310Gly) at O-domain was soluble at neutral pH.…”
Section: Methodsmentioning
confidence: 99%
“…Glucose, a representative PTS sugar, mediates transcriptional activation of several genes for PTS-related sugar transporters and some enzymes involved in glycolysis (1, 6). Mlc, a tetrameric protein (7), is a signaling mediator for glucose induction of several PTS operons and related genes (8)(9)(10)(11)(12)(13)(14).A unique feature of induction of the Mlc regulon by glucose is that the effector molecule modulating Mlc activity is a membranebound protein, EIICB Glc (7,15,16), in which cytosolic EIIB protein is attached to membrane-embedded EIIC protein through a linker of Ͼ20 aa. In the absence of glucose, EIICB Glc mainly exists in the phosphorylated form (pEIICB Glc ).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…It was shown that the ptsH P1 promoter is regulated by the repressor of the fructose PTS, FruR (12). Moreover, both the ptsH P0 promoter and the ptsG P1 promoter have been shown to be subject to activation by the cAMP⅐CRP complex and repression by Mlc (13)(14)(15)(16)(17)(18). Subsequently, it was demonstrated that the unphosphorylated form of EIICB Glc can relieve the repression of the Mlc regulon by sequestering Mlc through the direct protein-protein interaction to induce the expression of the Mlc regulon including PTS proteins (19 -21).…”
mentioning
confidence: 99%